2013
DOI: 10.1007/s00392-013-0615-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasomotor abnormalities in patients with stable angina after successful stent implantation but without in-stent restenosis

Abstract: Enhanced epicardial and microvascular coronary vasoconstrictions are frequently found in patients with stable angina after successful PCI but without significant ISR. Intracoronary acetylcholine provocation testing may be useful in these patients to determine the cause of angina and initiate appropriate medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 29 publications
1
39
0
3
Order By: Relevance
“…ACCEPTED MANUSCRIPT 8 We identified six RCTs that enrolled 3738 patients of which 1401 (37%) were randomized to EES and 2337 (63%) were randomized to BVS. The mean age was 66 years with 73% men and 45% with acute coronary syndromes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…ACCEPTED MANUSCRIPT 8 We identified six RCTs that enrolled 3738 patients of which 1401 (37%) were randomized to EES and 2337 (63%) were randomized to BVS. The mean age was 66 years with 73% men and 45% with acute coronary syndromes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[6,7] In addition, coronary vasomotion is reduced in the stented segment due to the metallic frames. [8] Bioresorbable vascular scaffolds (BVS) such as Absorb (Abbott Vascular, Santa Clara, California) offers an attractive option and a potential paradigm shift in device technology as they provide mechanical support and drug-delivery functions similar to those of DES, followed by complete bioresorption over several years. The potential advantage of BVS is the reduction in very late events (after one year), potential need for only a shorter duration of dual antiplatelet therapy, preserved coronary vasomotion after the resorbs and more importantly preserving the options for repeat revascularization (with either coronary artery bypass graft surgery or repeat percutaneous coronary intervention).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, percutaneous coronary intervention can be associated with coronary spasm. 42 However, it is still poorly understood whether coronary spasm can promote atherosclerotic alterations or whether the latter may predispose to spasm. There are several reports of structural alterations of the epicardial arteries in patients with vasospastic angina.…”
Section: Epicardial Arteriesmentioning
confidence: 99%
“…Initial studies showed restored vasomotion at the stented site and adjacent coronary segments in response to vasoactive agents [1]. It has been reported recently that recurrent angina after a successful percutaneous coronary intervention with metallic stents may be caused by functional vessel abnormalities [2].…”
Section: Introductionmentioning
confidence: 98%